1977
DOI: 10.1128/aac.12.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pharmacological and Antimicrobial Properties of Cefadroxil and Cephalexin

Abstract: Pharmacological and antimicrobial properties of cefadroxil, a new cephalosporin antibiotic, were compared with cephalexin. Absorption and excretion were studied in 20 healthy men. Peak concentrations of the drugs in serum were similar after ingestion of single 500-mg tablets. The concentration of cefadroxil in serum was more sustained than that of cephalexin. Levels of cefadroxil in serum after a dose of 1,000 mg were approximately twice those after a 500-mg dose through 6 h. Each drug administered in a dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In experimental infections in animals, CGP 9000 proved to be superior to cephalexin (27). The bioavailability of cephadroxil administered orally is superior to that of cephalexin (10,22). In the present study, the pharnacokinetic parameters of these three new substances and cephalexin were compared after oral administration to each of 12 fasting subjects.…”
mentioning
confidence: 92%
“…In experimental infections in animals, CGP 9000 proved to be superior to cephalexin (27). The bioavailability of cephadroxil administered orally is superior to that of cephalexin (10,22). In the present study, the pharnacokinetic parameters of these three new substances and cephalexin were compared after oral administration to each of 12 fasting subjects.…”
mentioning
confidence: 92%
“…The area under the serum concentration versus time curve is larger and bioavailability greater for cefadroxil [1,7], Our pharmacokinetic results are consis tent with those noted by other authors [5] who also found a peak serum level of 25-26/ig ml"1 at 1.59 h and elimination halflife of 1.51 h after ingestion of 1,000 mg of cefadroxil. The average elimination se rum half-life was 1.39 h and thus longer than that of cephalexin (0.9-1.1 h) [4,7] and two times longer than that of cephradine (0.6-0.7 h) [7], Like in other cephalospo rins, urinary elimination was very high, since 93.0% of the dose was recovered in the urine during the first 24 h; urinary con centrations of the antibiotic were conse quently very high. In patients with chronic renal insufficiency, the peak serum level of cefadroxil increased as soon as renal func tion decreased (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested earlier, cephalexin is well absorbed following a wide range (0.125-2.0 g) of oral doses administered as capsule, tablet, solution, or suspension (THORNHILL et al 1969;GOWER and DASH 1969;BERGAN et al 1970;GRIFFITH and BLACK 1971;O'CALLAGHAN et al 1971;LoDE et al 1979;BARRIOS et al 1975;Ac-TOR et al 1976a;PFEFFER et al 1977;HARTSTEIN et al 1977;HENNESS et al 1978;FINKELSTEIN et al 1978;CHOW et al 1979;BUSTRACK et al 1980;SIMON 1980 a;LE-CAILLON et al 1980;LODE et al 1980c). Peak serum concentrations of cephalexin occur within 1-2 h, dependent upon the formulation.…”
Section: Cephalexinmentioning
confidence: 88%
“…Thirty-eight percent to 58% of the dose was excreted unchanged in urine in 3 hand 85%-93% was recovered in 24 h. Regimens of 500-1,000 mg every 6 h did not lead to drug accumulation in serum, whereas 1,500 mg every 6 h led to a small amount of accumulation. The apparent serum half-life of cefadroxil appears to be approximately 1-1.5 h. Administration with food does not affect the plasma levels or urinary recovery ofcefadroxil (HARTSTEIN et al 1977;PFEFFER et al 1977;JOLLyet al 1977;HENNESS et al 1978;LoDE et al 1980c;SIMON 1980a;PRENNA and RIPA 1980). BUCK and PRICE (1977) determined the serum protein binding of cefadroxil to be 20% by ultrafiltration over a drug concentration range of 10-25 ~g/ml.…”
Section: Cefadroxilmentioning
confidence: 96%